São Paulo no cinema: traduções intersemióticas das práticas de vida na cidade - Nichile, Maria Cecília Ferreira de (2016)
In the last century, the city of São Paulo, as many other capitalist societies, has faced an accelerated development and has had an expressive growth of its population. Throughout this process, São Paulo cinema has been one of the medium used in the creation of intersemiotic translations of the impressions of its citizens about these transformations and the new ways of life that emerged. Thus, the objective of this dissertation is, from five contemporary films – Não por Acaso (2007), Linha de Passe (2008), Trabalhar Cansa (2011), Super Nada (2012) e Riocorrente (2013) – in analogy to other two movies from over fifty years ago – São Paulo, Sinfonia da Metrópole (1929), São Paulo Sociedade Anônima (1965) –, to analyze how the movies organize the cinematographic syncretic devices: the editing, the photography, the sound and the framing, with the intention to translate the urban experience through the filmic arrangement of figurativities and plasticities. By observing films of diverse periods, with different looks to the same city, this paper will examine which figurativities and themes are recurring or contradict themselves in the audiovisual translation of this metropolis, and how the actors, the temporality and the spatiality are enunciated in these storylines. It is through an analysis based on the semiotic theory, in particular the plastic semiotic and the socio-semiotic, and also the enunciation approach, that this study will verify if in these films, in analogy, São Paulo is shown as the subject that imposes its values to the population through its modern characteristics